2006
DOI: 10.1007/s10482-005-9028-8
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing system influences root colonization and biological control ability in Pseudomonas fluorescens 2P24

Abstract: Pseudomonas fluorescens 2P24 is a biocontrol agent isolated from a wheat take-all decline soil in China. This strain produces several antifungal compounds, such as 2,4-diacetylphloroglucinol (2,4-DAPG), hydrogen cyanide and siderophore(s). Our recent work revealed that strain 2P24 employs a quorum-sensing system to regulate its biocontrol activity. In this study, we identified a quorum-sensing system consisting of PcoR and PcoI of the LuxR-LuxI family from strain 2P24. Deletion of pcoI from 2P24 abolishes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 51 publications
4
91
0
1
Order By: Relevance
“…We therefore thoroughly tested root colonization of the different strains and showed that this trait is under positive QS regulation in P. aeruginosa PUPa3. This is similar to the results found for P. fluorescens 2P24, in which the QS mutant also showed a reduced capability for root colonization (60). Another report showing positive QS regulation of root colonization was for PGPR Pseudomonas chlororaphis strain 30-84; for this species it was suggested that production of phenazines, which are antibiotics produced by this strain, is under QS regulation.…”
Section: Discussionsupporting
confidence: 85%
“…We therefore thoroughly tested root colonization of the different strains and showed that this trait is under positive QS regulation in P. aeruginosa PUPa3. This is similar to the results found for P. fluorescens 2P24, in which the QS mutant also showed a reduced capability for root colonization (60). Another report showing positive QS regulation of root colonization was for PGPR Pseudomonas chlororaphis strain 30-84; for this species it was suggested that production of phenazines, which are antibiotics produced by this strain, is under QS regulation.…”
Section: Discussionsupporting
confidence: 85%
“…If generalist anti-B. dendrobatidis bacteria, such as pseudomonads, are important as an amphibian defense mechanism against B. dendrobatidis, then the abundance of these bacterial species may be a key factor in protection (54,55). In some cases, high cell density is needed to produce inhibitory metabolites because the metabolites are produced in high quantities only when bacteria form a biofilm and undergo quorum sensing (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 2,4-DAPG is a well-characterized compound due to its broad spectrum of activity and in situ inhibitory action on phytopathogens (Bangera & Thomashow, 1999). It functions as a major ingredient in biocontrol agents, such as Pseudomonas fluorescens strains Q2-87, F113, CHA0 and 2P24, used to protect crops against a number of plant diseases such as wheat take-all caused by Gaeumannomyces graminis, sugar beet seedlings dampingoff caused by Pythium ultimum, tobacco black root rot caused by Thielaviopsis basicola, cotton rhizoctoniosis caused by Rhizoctonia solani and tomato bacterial wilt caused by Ralstonia solanacearum (Bangera & Thomashow, 1999;Fenton et al, 1992;Schnider-Keel et al, 2000;Zhou et al, 2005;Wei & Zhang, 2006).…”
Section: Introductionmentioning
confidence: 99%